2011
DOI: 10.1037/a0021668
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and perspectives of African American, Latina/o, Asian American, and European American psychology graduate students: A national study.

Abstract: A national, web-based survey of 1,222 African-American, Latina/o, Asian-American and European-American psychology graduate students revealed both similarities and differences in experiences and perspectives. Mentoring was found to be the strongest predictor of satisfaction across groups. Academic supports and barriers, along with perceptions of diversity were also important predictors of satisfaction. Students of color differed from European-American students in perceptions of fairness of representation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(101 citation statements)
references
References 62 publications
4
97
0
Order By: Relevance
“…The result that a sense of relatedness to an advisor was positively related to motivation to continue and graduate student program satisfaction was not unexpected; the importance of the advisor has been documented in many other studies (Bair & Haworth, 1999Faghihi et al, 1999Lan & Williams;2005;Lovitts, 2001Lovitts, , 2008Maton et al, 2011;Paglis et al, 2006;Tenenbaum et al, 2011;Zhao et al, 2007). What was not studied in the investigation was a sense of relatedness to peers.…”
Section: Further Researchmentioning
confidence: 71%
See 3 more Smart Citations
“…The result that a sense of relatedness to an advisor was positively related to motivation to continue and graduate student program satisfaction was not unexpected; the importance of the advisor has been documented in many other studies (Bair & Haworth, 1999Faghihi et al, 1999Lan & Williams;2005;Lovitts, 2001Lovitts, , 2008Maton et al, 2011;Paglis et al, 2006;Tenenbaum et al, 2011;Zhao et al, 2007). What was not studied in the investigation was a sense of relatedness to peers.…”
Section: Further Researchmentioning
confidence: 71%
“…That is, doctoral students who felt a sense of relatedness with their advisor felt more satisfied with graduate school than those did not have that sense of relatedness with their advisor. Previous research also supports that mentoring and positive advisor relationships are positively related to graduate student program satisfaction (Maton et al, 2011;Nettles & Millett, 2006, chap. 11;Tenenbaum et al, 2001).…”
Section: Hypothesis 2: Autonomy Competence and Relatedness Will Be mentioning
confidence: 78%
See 2 more Smart Citations
“…Microaggressions may be unconsciously delivered and often take the form of subtle slights, snubs, and questions about one's ability and belonging (Solorzano, Allen, & Carroll, 2002;Solorzano, Ceja, & Yosso, 2000;Sue et al, 2007). Research found that the experience of microaggressions in academic and social spaces on campus negatively influences retention, perception of the campus climate, and academic success (Clark, Mercer, Zeigler-Hill, & Dufrene, 2012;Gomez, Khurshid, Freitag, & Lachuk, 2011;Maton et al, 2011;Nadal, Pituc, Johnston, & Esparrago, 2010;Solorzano et al, 2000;Van Ryzin, Gravely, & Roseth, 2009;Walton & Cohen, 2007;Yosso, Smith, Ceja, & Solorzano, 2009). Although microaggressions have not been studied specifically as they relate to graduate student sense of belonging, previous research suggests to us that they could negatively impact graduate student sense of belonging.…”
Section: Microaffirmations and Microaggressionsmentioning
confidence: 99%